(untitled) (Bangladesh Medical Journal, 2023)
Parry Romberg syndrome (PRS) is an acquired, rare, neurocutaneous disorder presenting most commonly as hemiatrophy of face with characteristic involvement of skin, subcutis, bone and denture with or without neurological manifestations.Here we present a case of 16 year old girl, who presented with characteristic insidious, progressive, selflimited hemifacial atrophy accompanied with headache and facial pain. Bangladesh Med J. 2021 Sept; 51(1): 59-62